(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
This scientific article presents a review of current knowledge on chronic kidney pathology, in particular chronic kidney failure, in both the pre- and post-transplantation periods, as well as pathological changes affecting the organs of the ear, nose, and throat.